The Moderating Impact of Individual Spirituality on the Relationship of Spiritual Leadership toward Individual Capability in the Form of Spirit at Work toward Organizational Objectives - Indrajaya, Amelia Naim; Afiff, Adi Zakaria; Balqiah, Tengku Ezni; Rahmawati, Riani (Sekolah Tinggi Manajemen IPMI, 2023)
This empirical research identifies the possible resources as antecedents of Spirit at Work (SW) in an RBV framework. The research empirically examines 530 data taken from a leading telco company on the interaction between organizational resources in the form of spiritual leadership (SL) variables: Vision, hope/faith, altruistic love (AL), meaning/calling and membership toward SW, and human resource in the form of Individual Spirituality (IS) toward SW. Further, SW is tested toward Job Satisfaction (JS) and Organizational Commitment (OC) as competitive advantages in the Service Industry.Findings show that all work related SL variables are significant toward SW. AL shows significant influence toward SW in the context of lower IS. The SW is also significantly and positively impacting JS and OC. Vision, AL and Membership which serve as the primary role and show dependence upon organizational support, are showing higher influence toward SW in lower IS. Hope/Faith and Meaning/Calling as secondary role which rely on employees’ intrinsic factors are showing higher influence toward SW in group of higher IS.